(untitled) (International Journal of Engineering and Computer Science, 2018)
Today, security is the main problem. Almost all the work is done over the internet crucial data are sent over the web and other information is placed over internet. While all the data is available online, there are many type of users who interact with data some of them for their need and others for gaining knowledge that how to destroy the data without the knowledge of the owner. There are various techniques used for protection of data but the hacker (or cracker) is more intelligent to hack the security, basically there are two categories of hackers that are different from each other on the basis of their intensions. The one who has good intensions are known as ethical hackers because they ethics to use their skill and techniques of hacking to provide security to the sensitive data of the organization. To understand this concept fully we describe introduction about the hacking, types of hackers, a survey of IC3, rules of ethical hacking and the advantages of the ethical hacking.